(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
In article structural-semantic features of designs with value of circumstances, situations and events in human life which are carried to посессивным to designs diffusios type on a designation of relations «posessiv– abstract concept» reveal. It is proved that analized designs are independent structural-semantic type posessiv units in the Ukrainian language.